الدولة الإسلامية والجهاد في زمن الحداثة: قراءة في المفاهيم والتجارب المعاصرة - المصطفى، حمزة مصطفى (المركز العربي للأبحاث ودراسة السياسات, 2016)
تسعى هذه الورقة إلى تقديم مقاربة جديدة لنشأة الحركات الجهادية عموما وتنظيم داعش خصوصا تختلف عما هو سائد في الأدبيات العربية والغربية، والتي عادة ما تربط دوافع نشأة هذه الحركات بالعودة إلى الماضي ونماذج الحكم التي كانت سائدة في القرون الوسطى. تفترض الدراسة أن مصطلح الدولة الإسلامية نشأ في إطار الاشتباك الإسلامي مع الحداثة والدولة الحديثة، وأنه في تعريفه الإجرائي لا يغدو عن كونه محاولة لأسلمة الدولة الحديثة. وعليه، فإن الحركات الجهادية التي تلقفت هذه المصطلح وكأنه مقابل مضاد للدولة الحديثة أنتجت مشروعا في سياق الحداثة والدولة الحديثة يختلف جذريا عما تصبو إليه، وقد برز ذلك عيانا في تجارب نسميها مجازا "دولتية" كما هي الحال مع تجربة طالبان في أفغانستان، وتجربة داعش حاليا.
This paper presents a new approach to the emergence of jihadist movements in general and the Islamic State (ISIL) in particular, an approach which differs from those prevalent in Arab and Western literature that usually links the motives behind the emergence of these groups to the return to the past and medieval models of government. This study assumes that the term "Islamic State" emerged in the context of Islam’s clash with modernity and the modern state, and that in its procedural definition it is no more than an attempt to Islamize the modern state. Accordingly, jihadist movements that have seized on this term, as if it were the opposite to the modern state, have produced a project in the context of modernity and the modern state that is radically different from their intended one. This is clear in experiences which we term «state-like», as was the case for the Taliban in Afghanistan and is presently the case for ISIL.
Keywords: تنظيم داعش -- الجهاد -- الحداثة -- الإسلام السياسي -- العلمنة